α-Hederin Saponin Augments the Chemopreventive Effect of Cisplatin against Ehrlich Tumors and Bioinformatic Approach Identifying the Role of SDF1/CXCR4/p-AKT-1/NFκB Signaling - Samah M. Elaidy; Mohamed K. El-Kherbetawy; Sally Y. Abed; Abdullah Alattar; Reem Alshaman; Mohamed Ahmed Eladl; Eman Saad Alamri; Aisha Nawaf Al balawi; AbdelNaser Zaid; Amany Y. Elkazzaz; Sozan M. Abdelkhalig; Ziad E. Hamed; et al. (Pharmaceuticals, 2023)
Stromal cell-derived factor-1 (SDF1) and its C-X-C chemokine receptor type 4 receptor (CXCR4) are significant mediators for cancer cells’ proliferation, and we studied their expression in Ehrlich solid tumors (ESTs) grown in mice. α-Hederin is a pentacyclic triterpenoid saponin found in Hedera or Nigella species with biological activity that involves suppression of growth of breast cancer cell lines. The aim of this study was to explore the chemopreventive activity of α-hederin with/without cisplatin; this was achieved by measuring the reduction in tumor masses and the downregulation in SDF1/CXCR4/pAKT signaling proteins and nuclear factor kappa B (NFκB). Ehrlich carcinoma cells were injected in four groups of Swiss albino female mice (Group1: EST control group, Group2: EST + α-hederin group, Group3: EST + cisplatin group, and Group4: EST+α-hederin/cisplatin treated group). Tumors were dissected and weighed, one EST was processed for histopathological staining with hematoxylin and eosin (HE), and the second MC was frozen and processed for estimation of signaling proteins. Computational analysis for these target proteins interactions showed direct-ordered interactions. The dissected solid tumors revealed decreases in tumor masses (~21%) and diminished viable tumor regions with significant necrotic surrounds, particularly with the combination regimens. Immunohistochemistry showed reductions (~50%) in intratumoral NFκβ in the mouse group that received the combination therapy. The combination treatment lowered the SDF1/CXCR4/p-AKT proteins in ESTs compared to the control. In conclusion, α-hederin augmented the chemotherapeutic potential of cisplatin against ESTs; this effect was at least partly mediated through suppressing the chemokine SDF1/CXCR4/p-AKT/NFκB signaling. Further studies are recommended to verify the chemotherapeutic potential of α-hederin in other breast cancer models.